DRAMATURGY: SCRIPT AND THEATER STAGE PERFORMED BY AMATEUR “ACTORS DIRECTED” AB ASMARANDANAPRAWIRA - Asep Wasta; Arni Apriani (Universitas Pendidikan Indonesia, 2022)
Performing art is the realization of working ideas as outlined by the creator in an art presentation that contains artistic aesthetics that can be enjoyed by the audiences.. Theatrical art is essentially from several art dimensions, including: dance (movement), fine arts, literary arts and music. This article examines the work of the theatrical play